Rational Selection of Mixed Yeasts Starters for Agave Must Fermentation - Larralde-Corona, Claudia Patricia; De la Torre-González, Francisco Javier; Vázquez-Landaverde, Pedro Alberto; Hahn, Dittmar; Narváez-Zapata, José Alberto (Frontiers in Sustainable Food Systems, 2021)
Tequila and mezcal are both traditional Mexican liquors that are produced from cooked Agave spp must fermentation, and usually rely on spontaneous or pure Saccharomyces cerevisiae strain inoculation. In order to contribute to the rational selection of yeast starters for tequila and mezcal productions, we tested a collection of 25 yeasts originally isolated from mezcal musts. These strains were first characterized in a semi synthetic medium (labeled as M2, having 90 g/l fructose and 10 g/l glucose of initial hexoses) at 48 h of culture, observing a differential pattern in the consumption of sugars and productivity. Selected Saccharomyces strains left around 10 g/l of fructose and showed higher fermentation performance. However, some non-Saccharomyces strains, specifically from Torulospora (Td), Kluyveromyces (Km) and Zygosaccharomyces (Zb) genera, consumed almost all the sugar (i.e. Km1Y9 with less than 5 g/l) and had a high productivity of ethanol. In general, all Saccharomyces strains presented a high production of ethyl-butyrate, ethyl-decanoate and ethyl-hexanoate with peaks of 10, 38 and 3 g/l, respectively. In addition, some Kluyveromyces and Torulospora strains showed a high production of phenyl ethyl acetate (i.e. Km1D5 with up to 1400 g/l); isoamyl acetate (i.e. Km1D5 and Td1AN2 with more than 300 g/l), and hexyl acetate (i.e. Td1AN2 with 0.3 g/l). Representative strains of the most productive genera (Saccharomyces. Torulospora, and Kluyveromyces) were selected to evaluate their fermentative performance and survival in a mixed culture on a medium based on Agave tequilana must, and their population kinetics were characterized using specific fluorescent in situ hybridization (FISH) probes in a qualitative and semi-quantitative analysis during fermentation. We observed that the mixture ratios of 0.1:1:1 or 1:1:1 (Saccharomyces : Kluyveromyces : Torulospora), maintained a good fermentation productivities, with alcohol yields above 0.45 g/g, and allowed a high survival rate of the non-Saccharomyces strains during fermentation process. Finally, mixed inoculum fermentations on Agave tequilana must medium, including different Saccharomyces strains and the finally selected Torulospora and Kluyveromyces strains, showed the best production parameters in terms of ethanol, carbon dioxide, glycerol, and acetic acid values, as well as improved volatile metabolite´s profiles as compared to the pure cultures.